iSpring Suite-Based Interactive Multimedia Development For Class V Volume Material Cube and Beam - Muhammad Fauzan; Yuli Witanto (JINoP (Jurnal Inovasi Pembelajaran), 2025)
The lack of variety in the use of media in learning can make students bored and learning becomes monotonous. Teachers still use teacher books, student books and learning media in the form of building spaces made of paper where the media is easily damaged. In fact, the use of the right media in the learning process can create a fun classroom atmosphere, so that students become active, creative, effective and get meaningful learning. The facilities provided by the school are also quite complete such as; Projectors, laptops as well as speakers and microphones are only used to the maximum. To maximize these facilities, the researcher wants to develop an interactive multimedia based on the iSpring Suite which aims to improve the learning outcomes of class V students of cube and block volume materials. This research method uses R&D research with the Borg and Gall development model consisting of 10 steps, but in its implementation the researcher only reaches the 8th step. The media created is then tested by material and media experts. The validation test was obtained as a result of the assessment according to material experts of 91.07% (very feasible) and according to media experts of 82.5% (feasible). In addition, after being used in learning, this media showed a significance result on the T-test of 23,723 and the N-gain test obtained a result of 0.7555 which was included in the high criterion. Based on the results of the study, it is shown that the use of interactive multimedia based on iSpring Suite is effectively used to improve student learning outcomes.